Immobilization of tetrabutyl thiuram disulfide in chitosan thin film for sensing zinc ion using surface plasmon resonance spectroscopy - Yap, Wing Fen; Mat Yunus, Wan Mahmood; Talib, Zainal Abidin (Scientific Publishing Division Myu, 2013)
Tetrabutyl thiuram disulfide (TBTDS) immobilized in chitosan thin film has been studied as a sensor element for zinc ion, Zn2+, using surface plasmon resonance (SPR). The TBTDS-immobilized chitosan thin film, which acts as an active layer, was coated on a gold film by spin coating. Zn2+ can be detected by measuring the SPR signal when TBTDS-immobilized chitosan thin film contacts with Zn2+ in solution. The sensor produced a linear response for Zn2+ ranging from 0.1 to 1 ppm with a sensitivity of 0.0317 degrees ppm(-1). Using immobilized TBTDS as an active layer, the Zn2+ can also be selectively detected when present in mixtures of heavy metal ions.